2011
DOI: 10.3945/ajcn.110.009266
|View full text |Cite
|
Sign up to set email alerts
|

No effect of antioxidant supplementation on muscle performance and blood redox status adaptations to eccentric training

Abstract: Background: It was recently reported that antioxidant supplementation decreases training efficiency and prevents cellular adaptations to chronic exercise. Objective: This study aimed to investigate the effects of vitamin C and vitamin E supplementation on muscle performance, blood and muscle redox status biomarkers, and hemolysis in trained and untrained men after acute and chronic exercise. A specific type of exercise was applied (eccentric) to produce long-lasting and extensive changes in redox status biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 44 publications
(62 reference statements)
6
133
1
4
Order By: Relevance
“…The duration of vitamins C and E administration was one week, shorter compared to previous reports with supplementation period with over three weeks [10,[12][13][14][15]18], however, proved that one week antioxidant vitamin administration could increase the plasma concentration of vitamin C. Plasma SOD was significantly decreased while GPx activity increased, resulting in an increase in the GPx/ SOD activity ratio. Although the indices of protein carbonyl and TBARS contents showed slight decreases, the differences were not significant.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The duration of vitamins C and E administration was one week, shorter compared to previous reports with supplementation period with over three weeks [10,[12][13][14][15]18], however, proved that one week antioxidant vitamin administration could increase the plasma concentration of vitamin C. Plasma SOD was significantly decreased while GPx activity increased, resulting in an increase in the GPx/ SOD activity ratio. Although the indices of protein carbonyl and TBARS contents showed slight decreases, the differences were not significant.…”
Section: Discussionmentioning
confidence: 67%
“…Vitamins C and/or E, despite protection against oxidative stress interfere with the adaptive responses to endurance exercise training [10]. Most of the studies have reported that vitamins C and/or E supplementation does not affect redox status [12][13][14], less have reported attenuation of oxidant stress [10,15], and there are reports indicating a pro-oxidant effect [14]. These differences between responses and adaptation to exercise possible indicate the complexity of redox biochemistry [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results did not support any effect of antioxidant supplementation. The complete lack of any effect on measures of physiological and biochemical results used, raises questions about the validity of the use of oral antioxidant supplementation as a redox muscle modulator and redox status in healthy humans [26].…”
Section: Effect Of Antioxidant Supplementationmentioning
confidence: 99%
“…78 Benzer şekilde Theodorou ve ark., E ve C vitamini takviyesinin kas hasarı, performans ve oksidatif strese etkisinin olmadı-ğını belirtmişlerdir. 79 Üç haftalık E vitamini takviyesinin direnç antrenmanlarının neden olduğu kas ağrısı, performans ve MDA seviyesine etkisinin olmadığı rapor edilmiştir.…”
Section: Geci̇kmi̇ş Kas Ağrisi Ve Anti̇oksi̇dan Kullanimiunclassified